Comparison of Standard and Modified Standard Organ Procurement - Koc, C; Akbulut, S; Yilmaz, S (2020)
Objectives: This study aimed to compare the impact of deceased-donor organ procurement techniques (standard versus modified standard) on biochemical outcomes after liver transplant. Materials and Methods: From February 2006 to December 2013, organs were recovered from 105 consecutive deceased donors by our transplant team. All organ procurement procedures were performed by a pioneer surgeon experienced in organ recovery from deceased donors. Donors were divided into those who had the abdominothoracic approach, which is referred to as the standard technique, and those who had the abdominal approach, which is referred to as the modified standard technique. Both groups were compared in terms of age, sex, weight, height, body mass index, liver graft weight, cross-clamping time, cold ischemia time, and liver function tests in recipients over the first 3 postoperative days. Results: Our study group included 66 male and 39 female donors, with an age range of 1 to 93 years (median of 44 y, means +/- standard deviation of 43.8 +/- 23.7 y). Among the deceased donors, 73 underwent the modified standard technique and 32 underwent the standard technique. There were no statistically significant differences between groups in terms of age, sex, weight, height, body mass index, graft weight, cold ischemia time, and liver function tests in recipients over the first 3 postoperative days. We observed a statistically significant difference between groups in terms of cross-clamping time (P < .001). Conclusions: Except for the decreased cross-clamping time, the modified standard technique for deceased organ retrieval had no effect on clinical outcomes in recipients after liver transplant. However, this retrospective study requires additional prospective investigations to more fully understand the differences. C1 [Akbulut, Sami] Inonu Univ, Fac Med, Dept Surg, Elazig Yolu 10 Km, TR-44280 Malatya, Turkey. [Akbulut, Sami] Inonu Univ, Fac Med, Liver Transplant Inst, Elazig Yolu 10 Km, TR-44280 Malatya, Turkey.